Discovering the communicative functions of cybertextual contexts in digital media environments: A sociosemiotic multimodal perspective - R. Kunjana Rahardi; Faizal Risdianto; Budi Purnomo; Ita Fitriana; Mezia Kemala Sari; Dian Rianita; Jumanto (Universitas Syiah Kuala, 2026)
Context plays a crucial role in language use, as it shapes the meaning of text interaction or communication. The exploration of the conceptualization of contexts in contemporary language studies, including cybertextual contexts, has long been debated among linguists. With the emergence of computer-mediated communication, social identity cues within cybertextual contexts have become an important area of inquiry. This research examined cyberpragmatics by analyzing textual environments through a socio-semiotic multimodal lens. Drawing on Leech’s perspective on general pragmatics, the notion of ‘context’ acquires a broader dimension, encompassing the circumstances surrounding digital interactions beyond the immediate social environment. This study employed online observation, expert-based selection, verification, classification, and interpretation to discover the communicative functions of the cybertextual contexts in the digital media environment. Based on a socio-semiotic multimodal analysis of six multimodality cybertextual contexts data, the findings identified six functions of cybertextual contexts: (1) providing background for intent delivery, (2) affirming intent delivery, (3) illustrating intent delivery, (4) shaping intent interpretation, (5) complementing intent conveyance, and (6) describing intent and meaning. Theoretically, this research highlighted the roles of visual, spatial, gestural, and aural contexts within cyberpragmatics. Empirically, this research illustrates the relationship between language and context in digital environments to uncover the evolving nature of communication in cyberspace.